The Reasons Behind the Belt and Road Initiative from Economic and Political Perspectives - Yang, Wanggan; Esedo, Kingsley; Hu, Weili; W. Johnson, Mary; Yang, Wangxin; Xin, Yongrong; Liu, Shouqiang; Collins, Eleanor (International Journal of Social Sciences: Current and Future Research Trends, 2023)
The Belt and Road Initiative was launched by Chinese President Xi Jinping in 2013 with the aim to rebuild the Silk Road and major Eurasian economies through infrastructure, trade and investment when he visited countries in Central Asia and Southeast Asia. This paper briefly introduces the Belt and Road Initiative. Then the paper discusses the rationales behind the belt and road initiative from economic and political perspectives. The author indicates that the China’s economy in a “new normal” and the tensions between China and the United States are two primary reasons behind the Belt and Road Initiative. Finally, the author raises the doubts of BRI’s sustainability due to previous Covid-zero policy and current Covid-19 outbreak in China.